Theoretical Framework of Stance: An Introduction of A New Analytical Category, Neutral Epistemic Stance - Sani Yantandu Uba; Mike Baynham (Yayasan Visi Intan Permata, 2018)
This paper extends Hyland’s (2005) theoretical framework of stance through the introduction of an additional analytic category of stance, neutral epistemic stance corresponding to Mushin’s (2001) factual epistemological stance. This article reviews various theoretical frameworks of stance and argues that none of these theoretical frameworks provide neutral linguistic markers of stance in academic writing. Using a corpus of twelve accounting PhD theses I conducted a textual analysis of different rhetorical sections between the theses, identifying what stance markers are used and why such stance markers are used and in what linguistic context such markers are used. This process led me to identify a new analytical category, neutral epistemic stance. This study contributes to the ongoing literature on stance in academic writing, arguing that unevaluated stance is also indicating taking up a neutral stance and can be understood as part of ‘doing objectivity’ in academic writing.